A Central Line Care Maintenance Bundle for the Prevention of Catheter-Associated Bloodstream Infection in Non-ICU Settings - O'Neil, Caroline (Infect Control Hosp Epidemiol, 2016)
OBJECTIVE: To evaluate a central line care maintenance bundle to reduce central line-associated bloodstream infection (CLABSI) in non-ICU settings. DESIGN: Before-after trial with 12 month follow-up period. SETTING: 1250-bed teaching hospital. PARTICIPANTS: Patients with central lines on eight general medicine wards. Four wards received the intervention and four served as controls. INTERVENTION: A multifaceted catheter care maintenance bundle consisting of educational programs for nurses, update of hospital policies, visual aids, a competency assessment, process monitoring, regular progress reports, and consolidation of supplies necessary for catheter maintenance. RESULTS: Data were collected for 25,542 catheter-days including 43 CLABSI (rate = 1.68 per 1,000 CL-days) and 4,012 catheter dressing observations. Following the intervention, a 2.5% monthly decrease in the CLABSI incidence density was observed on intervention floors, but this was not statistically significant (95% confidence interval (CI); −5.3 – 0.4). On control floors, there was a smaller, but marginally significant decrease in CLABSI incidence during the study (change in monthly rate = −1.1%; 95% CI, −2.1 - −0.1). Implementation of the bundle was associated with improvement in catheter dressing compliance on intervention wards (78.8% compliance pre-intervention vs. 87.9% during intervention/follow-up; p<0.001) but improvement was also observed on control wards (84.9% compliance pre-intervention vs. 90.9% during intervention/follow-up; P = .001). CONCLUSIONS: A multi-faceted program to improve catheter care was associated with improvement in catheter dressing care, but no change in CLABSI rates. Additional study is needed to determine strategies to prevent CLABSI in non-ICU patients.